PERILAKU KONSUMEN TERHADAP KEPUTUSAN MENGKONSUMSI PRODUK AGROINDUSTRI ABON IKAN LELE ORIGINAL - Ristina Siti Sundari; Dona Setia Umbara; Adnan Arshad (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Food diversification of fish in strengthening livelihood food security is getting priority, particularly during the COVID-19 pandemic. Almost all habits and behavior have changed. The scarcity and distribution gaps of the supply chain occurred, and hopefully, the new normal era will soon come. The research carried out to know the consumer behavior in decision making to consume diversification products of original catfish shredded and analyze the most dominant affected attribute. The research used the Rank Spearman Correlation Test toward interviewed 100 respondents. The result indicated that consumer behavior has an essential role in decision making to consume agribusiness diversification products of catfish shredded. The correlation is the more paying attention, the more consumer decided to consume catfish shredded. The product can distribute well. Analysis of organoleptic concluded that consumers refer to catfish shredded. It has a soft texture, refine the structure, delicious taste, and easy to chew, whereas catfish shredded had odor. Suggestion to advance research to eliminate catfish odor sensory.